Internalisasi Pendidikan Islam dalam Pengendalian Emosi Marah - Ulfa Kesuma (Institut Agama Islam Negeri Bengkulu, 2020)
Abstract: Internalization of Islamic Education in Controlling Angry Emotions. This study aims to describe how angry emotions can be controlled through the theory of Internalizing Islamic Education. Internalization of Islamic Education introduces 5 strategies in changing one's mindset and behavior including the exemplary strategy, the habituation strategy, the strategy of giving advice, the strategy of giving promises and threats and self-awareness. Through qualitative methods this study describes how the internalization of Islamic education is realized in the control of angry emotions. Interview and observation techniques (observations) are used by the author in studying how the internalization process takes place so that Islamic education has a role in controlling emotions. The conclusion is that exemplary strategies have a great effect in giving an example to individuals in controlling emotions, habitualizing strategies and giving advice are also needed in dealing with someone who is overflowing with angry emotions, bearing in mind that anger causes many negative effects such as saying harsh, cursing, damaging things to commit murder, besides that the promise and threat strategy also has a role in controlling angry emotions because if a person instills religious values in his heart and implements it will certainly remember that someone who can restrain his anger will benefit and be promised a heaven like the surrender of the good example. exemplified by the prophets. And no less important is self-awareness that limits one's emotional overflow.Abstrak: Internalisasi Pendidikan Islam dalam Pengendalian Emosi Marah. Penelitian ini bertujuan untuk mendiskripsikan bagaimana emosi marah dapat dikendalikan melalui teori Internalisasi Pendidikan Islam. Internalisasi Pendidikan Islam mengenalkan 5 strategi dalam mengubah pola pikir dan perilaku seseorang diantaranya adalah strategi keteladanan, strategi pembiasaan, strategi pemberian nasihat, strategi pemberian janji dan ancaman serta kesadaran diri. Melalui metode kualitatif penelitian ini mendiskripsikan bagaimana internalisasi pendidikan Islam tersebut terealisasi dalam pengendalian emosi marah. Teknik wawancara dan observasi (pengamatan) digunakan oleh penulis dalam mengkaji bagaimana proses internalisasi itu berlangsung sehingga pendidikan Islam memiliki peran dalam pengendalian emosi. Kesimpulannya bahwa strategi keteladanan memberikan efek yang besar dalam memberikan contoh kepada individu dalam mengendalikan emosi, strategi pembiasaan dan pemberian nasihat juga dibutuhkan dalam menghadapi seseorang yang sedang meluapkan emosi marah, mengingat bahwa marah menimbulkan banyak efek negatif seperti berkata kasar, memaki, merusak barang hingga melakukan pembunuhan, selain itu strategi janji dan ancaman juga memiliki peran dalam pengendalian emosi marah karena jika seseorang tersebut menanamkan nilai-nilai agama didalam hatinya serta mengimplementasikannya tentu akan mengingat bahwa seseorang yang dapat menahan marahnya akan mendapatkan keuntungan dan dijanjikan syurga seperti sabarnya suri tauladan yang dicontohkan oleh para nabi. Dan yang tidak kalah penting adalah kesadaran diri yang memberikan batasan terhadap meluapnya emosi seseorang